Laparoscopic Repair of a Rare Case of Bladder Rupture Due To Intravesical Explosion during Transurethral Resection of the Prostate - Adiyat, Kishore Thekke; Shetty, Abijit; T, Jayakrishnan (Urology Journal, 2014)
Intravesical explosion is an extremely rare event during TURP.(1) Though previously reported , all the cases were dealt by immediate laparotomy and bladder repair.(1) To our knowledge this is the first case where laparoscopy has been offered as a treatment option.